1994
DOI: 10.1093/ajcn/60.4.476
|View full text |Cite
|
Sign up to set email alerts
|

Satiety after preloads with different amounts of fat and carbohydrate: implications for obesity

Abstract: High intake of dietary fat may be key in both the etiology and maintenance of obesity. Because a reduction in the proportion of energy derived from fat will be accompanied by an increase in the proportion of energy derived from carbohydrate, this study compared the effects of these macronutrients on eating behavior in obese and lean individuals. The effects of different amounts of fat and carbohydrate, covertly incorporated into yogurt preloads, on subsequent food intake, hunger, and satiety were assessed. A g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
150
1
7

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(166 citation statements)
references
References 31 publications
8
150
1
7
Order By: Relevance
“…Consequently the effects of ED depend upon the nutrients supplying the energy. Other researchers have also noted that`Joule for Joule' fat is less satiating than CHO (Rolls et al, 1994). These ®ndings, in turn, are consistent with the notion that dietary macronutrients exert hierarchical effects on satiety, protein having the greatest effect and fat the least (Stubbs, 1995).…”
Section: How Does Varying the Ed Of The Diet (Using Different Composisupporting
confidence: 63%
See 1 more Smart Citation
“…Consequently the effects of ED depend upon the nutrients supplying the energy. Other researchers have also noted that`Joule for Joule' fat is less satiating than CHO (Rolls et al, 1994). These ®ndings, in turn, are consistent with the notion that dietary macronutrients exert hierarchical effects on satiety, protein having the greatest effect and fat the least (Stubbs, 1995).…”
Section: How Does Varying the Ed Of The Diet (Using Different Composisupporting
confidence: 63%
“…There are a number of examples which show that fat exerts detectable albeit relatively modest effects on appetite and EB which are independent of its contribution to dietary ED. CHO appears to exert a more acute effect on satiety than fat (Cotton et al, 1994), and three other studies have found this relatively subtle effect to be independent of ED (Rolls et al, 1994;Johnstone et al, 1996;Stubbs et al, 1997a). In one of these studies, the low satiating ef®ciency of fat in the short term appeared to be related to its low osmotic load, as indicated by the subjective thirst of the subjects .…”
Section: Energy and Nutrient Relationships Within Foods Ingested By Hmentioning
confidence: 93%
“…This seems to be in contrast with other studies (Barkeling et al, 1990;Porrini et al, 1995a,b). Probably, as reported by Rolls et al (1994), the impact of a preload on subsequent food intake diminishes with increasing time from the preload. In the present study there was a 7 h period between preload and test meal and this interval of time could have been too long to highlight differences in food consumption.…”
Section: Discussionmentioning
confidence: 60%
“…Although the lean participants in the current study consumed more than we had initially anticipated when fed the HF treatment, they did consume less than when they consumed only 20% of their ADER and, furthermore, they did exhibit greater control in consequent energy intake compared to their obese counterparts (Table 3). This ®nding is reinforced by the ®nding of Rolls et al (1994), which show that lean individuals exhibit a weak regulation in response to the ingestion of high-fat foods.…”
Section: Discussionmentioning
confidence: 92%
“…We hypothesize that obese males are less able to differentiate covert manipulation of energy content and control appetite than lean counterparts. As a corollary of testing this hypothesis, there was the ability to investigate possible metabolic and endocrinological factors contributing to the passive overconsumption observed with high-fat diets in the aetiology of appetite dysfunction leading to obesity (Rolls et al, 1994;Blundell & Macdiarmid, 1997). Although components of this question (ie the role of macronutrients on appetite regulation) have been previously addressed (Wooley et al, 1975) in lean females (Poppitt et al, 1998a), and in both lean male (Rolls et al, 1991;Stubbs et al, 1996) and lean female study participants (Rolls et al, 1991(Rolls et al, , 1994, as well as obese females (Rolls et al, 1994), to our knowledge, no study has combined these simultaneously with endocrine assessments in both lean and obese males.…”
Section: Introductionmentioning
confidence: 99%